Cover Feature: New Organometallic Ruthenium(II) Compounds Synergistically Show Cytotoxic, Antimetastatic and Antiangiogenic Activities for the Treatment of Metastatic Cancer (Chem. Eur. J. 66/2020). Issue 66 (6th October 2020) - Wang, Yuchen; Jin, Jiahui; Shu, Liwei; Li, Tongyu; Lu, Siming; Subarkhan, Mohamed Kasim Mohamed; Chen, Chao; Wang, Hangxiang
Abstract : Three birds with one stone : New therapies are needed to facilitate synergistic combinations that span distinct antitumor mechanisms. A small library of structurally relevant C, N‐cyclometalated ruthenium(II) complexes was synthesized and their pharmacologic efficacy was investigated. The cover art shows the structure of the complex Ru8, which was demonstrated to have three antitumor functions, including potent cytotoxicity, antimetastasis and antivascular activity. The complex deserves further investigation as a promising drug candidate to combat metastatic cancer. More information can be found in the Full Paper by C. Chen, H. Wang, et al. on page 15170 .